Response of drip water temperature to climate variability: a case study in Xiaoyan Cave, southwest China. Issue 7 (19th May 2019) - Guo, Xiaojiao; Gong, Xiaoping; Yuan, Daoxian; Jiang, Guanghui; Cao, Jianhua; Lin, Yushi; Lo, Kwong Fai Andrew; Chen, Changjie
ABSTRACT: Detailed monitoring of surface atmospheric and subterranean microclimatic conditions has provided a new opportunity to interpret drip water temperature changes associated with climate variability. High-resolution multi-index monitoring was conducted in Xiaoyan Cave, Guilin, southwest China, for a period of four years (2011–2014) to identify the processes that control drip water temperature. The results show that variations in drip water temperature are mainly coupled to changes in the cave air temperature unless large drip discharge occurs. The controls on cave air temperature depend on the ventilation modes that eventually affect drip water. The multiple thermal mechanisms are winter ventilation, heat conduction in summer and water flow-induced convection derived from subsurface water percolation into the cave due to fast preferential flow during heavy rain events. Drip water response to extreme temperature anomalies is shown to be sensitive to outside climate.